In-Hospital Formula Use Increases Early Breastfeeding Cessation Among First-Time Mothers Intending to Exclusively Breastfeed - Chantry, Caroline J. (2014)
OBJECTIVE: To evaluate in-hospital formula supplementation among first time mothers who intended to exclusively breastfeed and determined if in-hospital formula supplementation shortens breastfeeding duration after adjusting for breastfeeding intention. STUDY DESIGN: We assessed strength of breastfeeding intentions prenatally in a diverse cohort of expectant primiparae and followed infant feeding practices through day 60. Among mothers planning to exclusively breastfed their healthy term infants for ≥1 week, we determined predictors, reasons, and characteristics of in-hospital formula supplementation; and calculated the intention-adjusted relative risk (ARR) of not fully breastfeeding days 30–60 and breastfeeding cessation by day 60 with in-hospital formula supplementation (n=393). RESULTS: 210 (53%) infants exclusively breastfed during the maternity stay and 183 (47%) received in-hospital formula supplementation. The most prevalent reasons mothers cited for inhospital formula supplementation were: perceived insufficient milk supply (18%), signs of inadequate intake (16%), and poor latch or breastfeeding (14%). Prevalence of not fully breastfeeding days 30–60 was 67.8% vs 36.7%, ARR 1.8 [95% CI, 1.4–2.3], in-hospital formula supplementation vs exclusively breastfed groups respectively, and breastfeeding cessation by day 60 was 32.8% vs 10.5%, ARR 2.7 [95% CI,1.7–4.5]. Odds of both adverse outcomes increased with more in-hospital formula supplementation feeds (not fully breastfeeding days 30–60, P=.003 and breastfeeding cessation, P=.011). CONCLUSIONS: Among women intending exclusively breastfed, in-hospital formula supplementation was associated with nearly 2-fold greater risk of not fully breastfeeding days 30–60 and nearly 3-fold risk of breastfeeding cessation by day 60, even after adjusting for strength of breastfeeding intentions. Strategies should be sought to avoid unnecessary in-hospital formula supplementation and to support breastfeeding when in-hospital formula supplementation is unavoidable.